Boys Girls Total High School a 2 a M Middle School 2 b b N Total X Y T
In the table above, each letter represents the number of students in that category. Which of the following equals M − N ?
(A) X
(B) Y
(C) 3 ( Y − X )
(D) 3 T
(E) X + Y
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
M-N = 3a-3b We have: 3X = 3a+6b and 3Y = 6a+3b. So we eventualy have 3(Y - X) = 6a + 3b - 3a - 6b = 3a - 3b = M - N
We can start off by excluding the choices below for the provided reasons, given it is understood that we're looking for the total high school students minus the total middle school students:
*A * X represents the total boys in high school and middle school.
*B * Y represents the total girls in high school and middle school.
*E * X+Y represents the total boys and girls in high school and middle school, or in other words, T.
This leaves us with C and D .
*Choice D: * Here, 3 T represents the total divided by three. To check if this is equal to M-N, let us start off by evaluating M-N.
M = a + 2 a = 3 a N = 2 b + b = 3 b M − N = 3 a − 3 b
Next, lets evaluate 3 T and see if they're equal to one another.
3 T = 3 ( M + N ) M + N = ( a + 2 a ) + ( 2 b + b ) = 3 a + 3 b 3 T = 3 3 a + 3 b = a + b a + b = 3 a − 3 b
*Choice C: * So, lastly, we're left with the final choice. Before getting cocky and picking it right away, we'll evaluate it.
3 ( Y − X ) 3 [ ( 2 a + b ) − ( a + 2 b ) ] 3 ( 3 a − 3 b − a − 2 b ) 3 ( a − b ) 3 a − 3 b = 3 a − 3 b
There we have it, D is correct.
I think you meant choice C.
Problem Loading...
Note Loading...
Set Loading...
Correct Answer: C
Solution:
According to the table,
M = a + 2 a = 3 a
N = 2 b + b = 3 b
M − N = 3 a − 3 b
We analyze each of the answer choices:
(A) X = a + 2 b = 3 a − 3 b . Wrong choice.
(B) Y = 2 a + b = 3 a − 3 b . Wrong choice.
(C)
3 ( Y − X ) = = = 3 [ 2 a + b − ( a + 2 b ) ] 3 ( 2 a + b − a − 2 b ) 3 ( a − b ) = 3 a − 3 b = M − N .
Correct answer.
(D) 3 T = 3 M + N = 3 3 a − 3 b = a − b . Wrong answer.
(E) X + Y = a + 2 b + 2 a + b = 3 a + 3 b . Wrong answer.
Incorrect Choices:
(A) , (B) , (D) , and (E)
The Solution explains why these choices are wrong.